A tabu search heuristic for the vehicle routing problem with time deadlines and asymmetric distances - Ekmen, Pelin. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
Reducing transportation cost and meeting customer requirements on time are the two main targets of transportation, logistics, distribution and supply chain management. In this thesis, we focus on the Vehicle Routing Problem with Time Deadlines and Asymmetric Distances which appears as an application in transporting cash to ATMs. Two mathematical models are presented to solve this problem. Since large instances cannot be solved exactly, a metaheuristic method based on Tabu Search algorithm is also proposed to determine near-optimal routes by formulating a mixed integer linear model.The algorithm is tested on randomly generated asymmetric instances derived from the Solomon benchmark problem instances. They are solved by CPLEX 12.5 solver within GAMS suite 24.0 and compared with the results obtained by the Tabu Search heuristic. Furthermore, we convert some of Christofides et al. classical VRP test problems known as CMT in the literature available, and solve them by our algorithm. We compare our solutions with the best known results in the literature.
Keywords: Vehicle routing problem.